The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.24263/2304-974x-2018-7-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal concentration in edible fish muscle and water sample collected from different location in Chittagong: a public health concern

Abstract: Introduction. The research was carried out to investigate the concentration of heavy metals in fish and water samples collected from different locations of Chittagong District, Bangladesh. Materials and methods. The concentrations of heavy metals including Cr, Cu, Ni, Pb and Fe in sea water and marine fishes (pama croaker, bombay duck and rat-tail anchovy) were detected by using Air / Acetylene Flame Atomic Absorption Spectrophotometer along Chittagong City areas, Bangladesh. Results and discussion. The mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(Jezierska and Witeska 2006). The result from the comparison with other reported values showed that the degree of contamination in fishes of the study area was found lower from Buriganga and Turag river (Baki et al 2019 andAhmad et al 2016), Bay of Bengal (Jothi et al 2018) of the country while higher from the Dhaleshwari river (Ahsan et al 2018). The heavy metal concentrations in fishes from Kelanta river, Malaysia (Hashim et al 2014), Bay of Bengal, India (Mitra et al 2011, river Niger, Nigeria (Ujah et al 2017) were also higher than the present study.…”
Section: Cadmium (Cd)mentioning
confidence: 48%
“…(Jezierska and Witeska 2006). The result from the comparison with other reported values showed that the degree of contamination in fishes of the study area was found lower from Buriganga and Turag river (Baki et al 2019 andAhmad et al 2016), Bay of Bengal (Jothi et al 2018) of the country while higher from the Dhaleshwari river (Ahsan et al 2018). The heavy metal concentrations in fishes from Kelanta river, Malaysia (Hashim et al 2014), Bay of Bengal, India (Mitra et al 2011, river Niger, Nigeria (Ujah et al 2017) were also higher than the present study.…”
Section: Cadmium (Cd)mentioning
confidence: 48%
“…The Chattogram coastal water might be highly polluted with arsenic. It could be associated to effluent discharges from a major industrial and siderurgic plant near the sea and to agro-industrial activities, mainly run off from agricultural soils where fertilizers are used and other waste [14].…”
Section: Organ and Species Wise Arsenic (As) Lead (Pb) And Chromium (...mentioning
confidence: 99%
“…In many studies, fishes were the subject of investigation on metal accumulations and monitoring programs in seas or fresh water, due to their importance in human nutrition [12,13,14]. Such interest aimed at ensuring the safety to the food supply and minimizing the potential hazard effect on human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation